CORE CRYSTALLIZATION AND SILICATE-METAL MIXING IN THE PARENT BODY OF THE IVA IRON AND STONY-IRON METEORITES - Scott E.R.D.; Haack H.; McCoy T.J. (My University, 1996)
We have analyzed metallic and silicate phases in the IVA iron meteorites and two related stony irons, Steinbach and Sao Joao Nepomuceno. Analyses of bulk metal phases in the two stony irons using INAA show that they plot as close to the chemical trends within group IVA as most IVA irons, indicating a common source. Our fractional crystallization models for the IVA chemical trends suggest that the irons crystallized from a metallic melt that initially contained 2.5 +/- 1 wt% S. After S concentrations in the liquid reached 6 wt%, liquid trapping during crystallization increased the apparent distribution coefficient for S, as in group IIIAB. Compositions of the metal fractions in Steinbach and Sao Joao Nepomuceno match the calculated solid compositions after 50 +/- 10% and 80 +/- 10%, respectively, of the metallic melt had crystallized. We confidently conclude that the IVA irons and metal in the two stony irons were derived from the core of a single asteroid that fractionally crystallized. The wide range of metallographic cooling rates of IVA irons cannot result from crystallization in isolated pools in one or more bodies, as some authors have argued. Large depletions of Ga, Ge, and other moderately volatile elements in group IVA are unlikely to result from planetary processes; they may have been inherited from chondritic precursor material.The two IVA stony irons contain up to 60 vol% of a unique, coarse-grained mixture of tridymite, orthobronzite, and clinobronzite. Silicate-metal textures resemble those in rounded-olivine pallasites; both may result from the depression of cumulate silicates into underlying molten S-rich metal. Two IVA irons contain rare plate-like, silica crystals up to 10 mm long, but these occurrences seem unrelated to the stony-iron silicates. Because of the difficulty in forming the stony irons in an isolated, slowly cooling asteroid, we infer that they may have formed during the breakup and reassembly event invoked by Haack et al. (1995) to account for the fast cooling of Steinbach from 1200°C.